GLP-1 Receptor Agonists in Alcohol Use Disorder: Neurobiological Mechanisms and Therapeutic Potential - Czach, Zuzanna; Bachurska, Dominika; Ignarska, Magdalena; Ignarska, Justyna; Grygorczuk, Oliwia; Krzyżanowska, Karolina (Journal of Education, Health and Sport, 2025)
Alcohol use disorder (AUD) remains a significant global health challenge, characterized by compulsive alcohol intake, impaired control over consumption, and a high risk of relapse. Despite its widespread impact, pharmacological treatment options for AUD are limited and often insufficient. Glucagon-like peptide-1 receptor agonists (GLP-1RAs), originally developed for the treatment of type 2 diabetes and obesity, have recently gained attention for their potential to modulate reward-related behaviors and neurobiological pathways implicated in addiction. Preclinical studies in rodent models have demonstrated that agents such as dulaglutide, semaglutide, and liraglutide can reduce alcohol intake, reverse neurochemical disruptions in key brain regions, and alleviate anxiety and cognitive impairments associated with chronic alcohol exposure. These findings are supported by emerging clinical evidence, including randomized controlled trials and large-scale cohort studies, which suggest that GLP- 1RAs—particularly semaglutide—may reduce alcohol consumption and alcohol-related hospitalizations, especially in individuals with coexisting metabolic conditions. Although further randomized trials are needed to establish causality and define optimal treatment populations, GLP-1RAs hold substantial promise as a novel pharmacological approach in the treatment of AUD.